Development of E-Learning System to Support Informatics Learning at Secondary School Level - Moh. Nur Zamzami Zamzami; Siti Sendari; Yudhi Christianto; Yudhistira Wirayudha; Kanzul Fikri Fauzi (Fakultas Ilmu Sosial dan Humaniora, Universitas Ibrahimy, 2025)
The rapid advancement of information and communication technology (ICT) has significantly transformed the educational landscape, particularly in the implementation of e-learning systems. This study aims to develop an integrated e-learning system to support Informatics learning at the senior high school level, with a case study at SMA Negeri 8 Malang. The need for this development stems from the limited use of interactive digital platforms in current teaching practices, particularly for subjects requiring problem-solving and computational thinking such as Informatics. The research adopts a Research and Development (R&D) method, utilizing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Data were collected through observations, interviews, and questionnaires involving teachers, students, and IT staff. The results indicate that the developed e-learning system enhances student engagement, supports independent learning, and facilitates the integration of project-based and experiential learning approaches. The study also highlights challenges in infrastructure and human resources, including the need for continuous teacher training and technical support. This research contributes to the growing body of knowledge in digital education and provides practical recommendations for implementing effective e-learning systems in secondary schools.